DEVELOPMENT OF CALOTROPIS/COTTON BLENDED YARN AND ITS PROPERTIES - REEMA BORA*, SARADI JYOTSNA GOGOI and BINITA B. KALITA, (The Journal of Research ANGRAU, 2023)
Natural fibres, which are an important part of the human environment, and also valuable raw materials used for textile and non-textile production. The use of natural fibres instead of materials such as glass fibres, carbon, and talc provides several advantages including low density, low cost, good specific mechanical properties, and biodegradability. Blending is the mixing of two or more masses of fibres so that the resulting mixture has the characteristics of the average of the component items. The most important reason for blending is the creation of new and more desirable effects.This study was conducted in Assam in the year 2021. Four different methods were used for the extraction of fibre from the peeled bark of tender stems of Calotropis gigantea plants and among which chemical retting with alkali (NaOH) was selected for the study. The study was carried out by blending Calotropis and cotton in three proportions (25:75, 50:50, and 75:25 ratios) and the properties of blended yarns were investigated. It was observed that the Cotton yarn has given a higher amount of TPI and extension than the blended yarn. Fifty: fifty blended yarn have higher tensile stress, and higher lea strength than the other yarn, and were the finest among the blends.The cotton yarn had a finer count, high lea strength, and more count strength product compared to blended yarns. It was also noticed that 50:50 blended yarn had high count strength product than the other combination.